Effect of steel fibers on the failure of early age reinforced concrete beam - Arslan, Abdussamet; Ulucan, Zulfu Cmar (Turkish Chamber of Civil Engineers, 1997)
The main aim of the present work is the investigation of the effect of steel fibers on the handlability of concrete members. The early age behaviour of concrete members were proposed to improved by the incorporation of small quantities of inert steel fibers within the concrete mix. A series of concrete specimens with steel fibers were tested. The crack spacing, width and number were recorded against load for both ordinary and fiber reinforced concrete beams. It has been observed that the steel fiber reinforcement reduces the crack widths and the deflections of early age concrete beams subjected to flexure. The ultimate loads were observed to be increased, indicating an improved tensile capacity as a result of the inclusion of fibers. It was concluded that the economy of the precast concrete industry may be increased in the application of steel fiber reinforced concrete reduce the defective production.
Celik liflerin erken yastaki betonarme kirislerin gocmesine etkisi
Keywords: Bearing capacity; Concrete beams and girders; Cracks; Deflection (structures); Economics; Failure analysis; Fiber reinforced materials; Inclusions; Reinforced concrete; Steel; Structural loads; Tensile properties; Steel fiber reinforced concrete; Tensile capacity; Ultimate load; Structural analysis